Cross-Cultural Adaptation and Reliability of a Filipino Dry Eye Screening Questionnaire - Frances Marie DC. Roa-Lingad, MD; Ruben Lim Bon Siong, MD (Philippine Journal of Ophthalmology)
Objective: The objectives of this study were to develop a cross-culturally adapted, Filipino version of the Ocular Surface Disease Index (OSDI) questionnaire and to assess its reliability.